Efficient intra‐mode decision algorithm skipping unnecessary depth‐modelling modes in 3D‐HEVC. Issue 10 (1st May 2015) - Park, Chun‐Su
Abstract : The three‐dimensional (3D) extension of the high‐efficiency video coding (3D‐HEVC) standard adopts new depth‐modelling modes (DMMs) to provide an alternative prediction scheme for depth‐map intra‐coding. In 3D‐HEVC, although edges in depth maps can be accurately estimated by utilising the DMMs, testing the DMMs in the mode decision introduces a huge computational load to the encoder. A fast mode decision algorithm is proposed that can significantly reduce the computational overhead incurred by the DMMs. Experimental results indicate that the proposed algorithm reduces the encoding complexity by 33.89% on average without any penalty in coding efficiency.